Five-Year Follow-Up of a Cordotomy - Jan J Meeuse; Arnoud CM Vervest; Johannes H van der Hoeven; An KL Reyners (Pain Research and Management)
Percutaneous cervical cordotomy is an invasive procedure to treat severe, opioid-resistant cancer pain. It is usually proposed for patients with a limited life expectancy. As a consequence, objective quantification of the long-term effects of this procedure is lacking. The present report describes a patient who was treated with a right-sided percutaneous cervical cordotomy for refractory cancer pain. Afterward, disseminated seminoma was diagnosed, which was cured with chemotherapy. Five years after the procedure, a qualitative and quantitative evaluation of the long-term effects was performed. Sensory dysfunction was observed in the left side of the body, but no motor neuron or autonomic dysfunction was observed. The influence of these long-term effects on the patient’s daily activities was limited.